2017
DOI: 10.1371/journal.pone.0175933
|View full text |Cite|
|
Sign up to set email alerts
|

Honey bees preferentially consume freshly-stored pollen

Abstract: Honey bees (Apis mellifera) collect and store both honey and pollen in preserved forms. Pollen storage involves the addition of honey or nectar and oral secretions to pollen granules. It is controversial whether the duration of pollen storage alters the palatability or nutritive value of the pollen storage medium. We examined how bees utilize different-aged stored pollen during an extended pollen flow. The deposition of pollen into wax cells and subsequent consumption were monitored daily on 18 brood frames fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 71 publications
2
45
0
Order By: Relevance
“…A recent study found that among 6 geographically disparate apiaries in the US, 79 different pesticides and metabolites were observed, with up to 10 distinct modes of action 27 . While wax and honey can last for many months or even years, bees prefer pollen <72 h old 28 , so it would more likely reflect the hive's recent environment than wax or honey. In both August and October, beebread samples from the AG sites had more compounds (13.3 and 11.8, respectively) than either those in CA (11 and 5.8, respectively) or MT landscapes (7 and 8, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that among 6 geographically disparate apiaries in the US, 79 different pesticides and metabolites were observed, with up to 10 distinct modes of action 27 . While wax and honey can last for many months or even years, bees prefer pollen <72 h old 28 , so it would more likely reflect the hive's recent environment than wax or honey. In both August and October, beebread samples from the AG sites had more compounds (13.3 and 11.8, respectively) than either those in CA (11 and 5.8, respectively) or MT landscapes (7 and 8, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…These glands produce the proteinaceous secretions that nurse bees use to provision members of the hive including developing larvae and the queen [25,35,36]. Bee bread is made by mixing pollen, honey, and honey bee salivary secretions that contain bacteria commonly found in the honey bee digestive track [3739]. Cage studies have shown that while honey bees can survive and develop their HPGs and other tissues when fed artificial sources of protein, consuming bee bread results in the most developed HPGs [40,41].…”
Section: Introductionmentioning
confidence: 99%
“…Stored pollen harbors very few bacteria and can be considered a preservation environment evolved to minimize microbial growth and prevent spoilage (Anderson et al., ). Moreover, honey bees prefer to consume freshly collected pollen (Carroll et al., ). Glucose and leucine are absorbed in the anterior two‐thirds of the midgut, suggesting that host digestion concludes in this region (Crailsheim, a, ).…”
Section: Introductionmentioning
confidence: 99%